2005
DOI: 10.1038/ja.2005.5
|View full text |Cite
|
Sign up to set email alerts
|

A γ-Lactone Form Nafuredin, Nafuredin-γ, also Inhibits Helminth Complex I

Abstract: Nafuredin, a d -lactone antibiotic, is a fungal metabolite showing selective helminth NADH-fumarate reductase inhibition, and whose target had been revealed as complex I. We found that nafuredin is easily converted to nafuredin-g by weak alkaline treatment. The structure of nafuredin-g was elucidated as a g -lactone form of nafuredin with keto-enol tautomerism. Nafuredin-g shows similar complex I inhibitory activity as nafuredin, and it also possesses anthelmintic activity in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…1 A total synthetic study of 1 subsequently identified a novel and structurally simpler γ-lactone compound, nafuredin-γ (2), which was generated from 1 under mild basic conditions. [4][5][6] Moreover, the nematode complex I inhibitory activity of 2 was identical to that of 1. Therefore, nafuredin (1) and nafuredin-γ (2) holds promise as a selective antiparasitic agent.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…1 A total synthetic study of 1 subsequently identified a novel and structurally simpler γ-lactone compound, nafuredin-γ (2), which was generated from 1 under mild basic conditions. [4][5][6] Moreover, the nematode complex I inhibitory activity of 2 was identical to that of 1. Therefore, nafuredin (1) and nafuredin-γ (2) holds promise as a selective antiparasitic agent.…”
Section: Introductionmentioning
confidence: 74%
“…(( (2E,6E,10E) 7,11,6,10, sulfonyl)benzene (14) To a solution of geranyl geraniol (43.1 mg, 0.148 mmol) in Et 2 O (3.0 ml) at 0°C was added PBr 3 (7 μl, 0.0742 mmol). After stirring for 2 h at 0°C, the resulting mixture was quenched with cold water and the aqueous phase was extracted with a 1:1 Et 2 O:hexane mixture.…”
Section: (R)-5-methyl-1-((s)-2-methyltetrahydrofuran-2-yl)hex-4-en-1-mentioning
confidence: 99%
“…as an inhibitor of acyl-CoA: cholesterol acyl transferase (ACAT) [14]. There is a closer structural resemblance, at least in size, if not in oxidation state to nafuredin-g , a degradation product of another fungal metabolite from Aspergillus niger FT-0554, and shown to selectively inhibit helminth NADH-fumarate reductase [15]. Perhaps the closest structural relatives are the aurafurons A, EB and ZB isolated from the myxobacteria Stigmatella aurantiaca and Archangium gephyra [16].…”
Section: Resultsmentioning
confidence: 99%
“…NFRD activity was measured as described previously [24]. The other enzyme assays were performed as described previously [4].…”
Section: Biological Studiesmentioning
confidence: 99%